2020
DOI: 10.1186/s13052-020-0782-z
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation, infection, and allergy of upper airways: new insights from national and real-world studies

Abstract: The upper airways (UA) should be considered as a functional unit. Current functional anatomy divides URT in three, mutually dependent, "junction boxes": i) the ostio-meatal complex (OMC), ii) the spheno-ethmoidal recess (SER), and iii) the rhinopharynx (RP). Correct ventilation and effective mucociliary clearance of these sites significantly affect the healthy physiology of the entire respiratory system. The OMC, SER, and RP obstruction is the first pathogenic step in the inflammatory/infectious cascade of UA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 133 publications
(138 reference statements)
1
10
0
Order By: Relevance
“…Allergic asthma is usually characterized by early onset [ 38 ], whereas non-allergic and T2-low asthma is more frequently associated with obesity and old age [ 39 , 40 ]. This study confirmed the association between T2-high asthma and its severity [ 41 ], that could be explained by upper airways comorbidity [ 42 ].…”
Section: Discussionsupporting
confidence: 85%
“…Allergic asthma is usually characterized by early onset [ 38 ], whereas non-allergic and T2-low asthma is more frequently associated with obesity and old age [ 39 , 40 ]. This study confirmed the association between T2-high asthma and its severity [ 41 ], that could be explained by upper airways comorbidity [ 42 ].…”
Section: Discussionsupporting
confidence: 85%
“…Bacterial interference through Local Bacteriotherapy ma be envisaged a feasible, harmless, and reliable approach. Local administration of natural compounds represents an opportunity of directly modulating the immune response, which may be impaired by several environmental or individual factors [55]. The bacteriotherapy approach's rationale is the local persistence of safe bacteria, which competitively exclude or inhibit the growth of pathogens without unbalancing the existing ecosystem [56].…”
Section: Resultsmentioning
confidence: 99%
“…Number of trials had been conducted for treating upper airway disorders such as allergic rhinitis, nasal polyps, and chronic rhinosinusitis for which several therapeutics such as omalizumab, mepolizumab, dupilumab, a monoclonal antibody targeted toward IgE, an anti-IL-5 agent, anti-IL-4, and IL-3 had been used. The outcomes of the trials were positive [38]. Several other modern drugs have been discovered and synthesized in the laboratory with promising results.…”
Section: Current Clinical Practice and Approved Drugsmentioning
confidence: 99%